Reaction Mechanism in Standardized α-Cellulose Content Test: Study from Boehmeria nivea Fiber - Rahmawati, Fani; Basuki, Rahmat; Fahri, Mirad; Apriliyanto, Yusuf Bramastya; Kurniadi, Tedi; Nareswari, Vania Agatha; Sandri, Azzahra; Istiqomah, Tiara (Indonesian Scholar Society, 2024)
In defense industry, α-cellulose is the main component of nitrocellulose propellant. However, a detailed description of the reaction mechanism of each treatment step in SNI 0444-2009 is still very scarce. This study addresses this gap by presenting the reaction mechanisms of each treatment and the symbols used in the SNI 0444-2009 procedure. The separation of lignin from α-cellulose occurred by breaking the C‒O bond linking them. This bond was broken by the ‒OH group of NaOH via a hydrolysis reaction. The reaction was initiated with the elimination of a hydrogen atom from the lignin structure by the hydroxyl ion (‒OH), and the C‒O bond was broken by a hydrolysis reaction. The breaking of this bond was indicated by the disappearance of the IR peaks at wavenumbers 1049 and 1190 cm–1 in the filtrate after extraction. The SNI 0444-2009 method for the α-cellulose content test was carried out by a redox back titration of Cr(VI) with Fe(II) from ferrous ammonium sulfate. This titration was conducted to calculate the amount of Cr(VI) ions in potassium dichromate or Cr(VI) that did not react with lignin or beta cellulose in the filtrate. Understanding the contribution and reaction mechanisms of each compound involved in the SNI 0444-2009 procedure contributed to obtaining accurate data on α-cellulose content. In this study, the calculated α-cellulose content of the flax fiber was 96.75%. Furthermore, the detailed mechanism of the redox reaction was discussed in detail in this paper.